Spatial distribution of meso- and macro-zooplankton in the Bransfield Strait and around Elephant Island, Antarctic Peninsula, during the 2019–2020 austral summer - Criales-Hernández, María Isabel; Jerez-Guerrero, Mauricio; Latandret-Solana, Sadid A.; Gómez-Sánchez, Miguel Diego (Polar Science, 2022)
The Antarctic Peninsula is a region of the world where drastic impacts of climate change have been observed over the past few years, leading the communities inhabiting this area to adapt to new conditions. This is reflected in changes to the composition and abundance of pelagic species, especially zooplankton, which constitute the main food source for the trophic web supporting the ecosystem in this region. In this study, we compared the composition, abundance, and spatial distribution of meso- and macro-zooplankton and how they relate to the oceanographic conditions of the Bransfield Strait and the area surrounding Elephant Island, Antarctic Peninsula, during the 2019–2020 austral summer. The community was represented by three groups: small-sized copepods such as Oithona similis and Ctenocalanus citer, salps such as Salpa thompsoni, and the Euphausiacea. Euphausiacea showed an important decrease in composition and abundance and was only represented by Euphausia superba and Thysanoessa macrura. An increase in the abundance and distribution of S. thompsoni was observed over the entire study area, as well as positive SST anomalies, which possibly favored the increase in the S. thompsoni population, as well as the decrease and displacement of Euphausiacea adults and juveniles. If, as climate models predict, increases in temperatures keep occurring, our results reflect the scenario that will prevail for zooplankton in the Antarctic Peninsula, with effects on distribution and abundance that will lead to the dominance of species that are more successful in warmer conditions. journal article